2021
DOI: 10.1111/infa.12447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of social evaluation in infancy: A preregistered exploration of infants’ eye‐movement and pupillary responses to prosocial and antisocial events

Abstract: Past research shows infants selectively touch and look longer at characters who help versus hinder others (Social evaluation by preverbal infants. Nature, 2007, 450, 557; Three-month-olds show a negativity bias in their social evaluations. Developmental Science, 2010, 13, 923); however, the mechanisms underlying this tendency remain underspecified. The current preregistered experiment approaches this question by examining infants' real-time looking behaviors during prosocial and antisocial events, and explorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 84 publications
3
17
0
Order By: Relevance
“…The current study did not find a group-level helper preference in either age group. These results are consistent with some recent findings using the hill paradigm ( Cowell and Decety, 2015 , Schlingloff et al, 2020 ; but see positive evidence in Hamlin, 2015 ; Loheide-Niesmann et al, 2021 ; Tan and Hamlin, 2021 ). While acknowledging the inconsistencies in infants’ helper preferences to date, we view infants’ failure in the current studies as relatively unsurprising.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study did not find a group-level helper preference in either age group. These results are consistent with some recent findings using the hill paradigm ( Cowell and Decety, 2015 , Schlingloff et al, 2020 ; but see positive evidence in Hamlin, 2015 ; Loheide-Niesmann et al, 2021 ; Tan and Hamlin, 2021 ). While acknowledging the inconsistencies in infants’ helper preferences to date, we view infants’ failure in the current studies as relatively unsurprising.…”
Section: Discussionsupporting
confidence: 93%
“…That is, by the time infants entered the choice task they were already quite inattentive and fussy; many infants failed to choose between the characters at all. Therefore, and given recent evidence that even younger, 5-month-old infants show visual preferences for the helper after sufficient exposure to the very same cartoon hill stimuli in a behavioral paradigm ( Tan and Hamlin, 2021 ), we suspect that the manual choice measure in the current study was not a particularly reliable or valid measure of infants’ social preferences.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These findings shed light on the bases of infants' and toddlers' evaluations of helpers. Although past research has found that infants prefer agents who help others over agents who hinder others (Hamlin et al, 2007, 2010; Hamlin & Wynn, 2011; Margoni & Surian, 2018), there has been debate as to whether younger infants' preferences for helpers reflect an understanding of acts of helping as social actions that facilitate other agents' goals (Tan & Hamlin, 2022), or an understanding of communicative signals of a helper's desire for social engagement, observed when a social agent expresses positive affect, imitates others, or synchronizes its behavior with others' actions (Powell & Spelke, 2018a, 2018b; Scarf et al, 2012). Although multiple factors can influence infants' evaluations, the present studies show that when infants and toddlers first view a protagonist who engages in means‐end or direct actions on objects, their social evaluations depend in part on their understanding of the plans guiding the agent's actions.…”
Section: Discussionmentioning
confidence: 99%
“…Although infants' evaluations of helpers are consistent with an understanding of a protagonist's goal (see Tan & Hamlin, 2022), infants may favor helpers for at least two other reasons. First, infants may prefer helpers because their actions elicit positive affect from others.…”
Section: Developmental Changes In Hierarchical Action Planning and Go...mentioning
confidence: 99%